KORELASI KUALITAS TIDUR DENGAN FUNGSI KOGNITIF PADA LANSIA DI DESA TONJA DENPASAR - Yuliantry Indah Lestari,* Desak Ketut Indrasari Utami,* I Gusti Ngurah Budiarsa,* I Putu Eka Widyadh (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION PHYSIOLOGICALLY THE LEVEL OF MELATONIN WILL DECREASE WITH THE INCREASING OF AGE THUS CREATING IMPAIRED QUALITY OF SLEEP AMONG ELDERLY IMPAIRED QUALITY OF SLEEP THOUGHT TO BE ASSOCIATED WITH IMPAIRED COGNITIVE FUNCTION BUT RESEARCH ON THE RELATIONSHIP BETWEEN THE THOSE TWO IN INDONESIA ARE RARELY REPORTED